Children's perspectives and attitudes towards Fortnite 'addiction'. (August 2020) - Carter, Marcus; Moore, Kyle; Mavoa, Jane; gaspard, luke; Horst, Heather
Playing digital games is increasingly pathologized as an addiction or a disorder, but there is limited research into the impact of game addiction discourse on children who play digital games. In this article, we present results from a study into the digital play of twenty-four 9–14-year-olds, attending to our participants' perspectives and attitudes towards 'game addiction' and how it interacts with their play and identity. Focused primarily on the online multiplayer first-person shooter game Fortnite, we examine how children encounter and attempt to negotiate game addiction discourse and demonstrate how the discourse in and of itself produces challenges for young people whose interests and passions revolve around games. This article subsequently discusses how the discursive frameworks that are perpetuated in the media around 'problematic play' need to incorporate and be inclusive of the child's right to play, and the relevance of our findings to the study of media panic and children's critical media literacies.